Analisis CO2 Pertumbuhan Mikro Alga Hijau dengan Menggunakan Fermentor dalam Tanki Tertutup - Bahagia Bahagia; Vera Viena (Fakultas Teknik, 2019)
Microalgae are photosynthetic microorganisms with varying cell morphology, both unicellular and multicellular (forming small colonies). This research is about CO2 for the growth of green microalgae by cultivating algal strains in tank type reactors or fermenters. The study included optimization of the productivity of green algae in the capture of CO2 which can be used as a greenhouse gas catcher. Green algae were isolated from several waters in Banda Aceh. These microalgae species are isolated and have been identified, then cultivated in irradiated tank containers with 4 fluorescent lamps (2x8 watts; 4x8 watts) installed on the outside of the tank. This study evaluated the comparison of the growth of aerated microalgae O2 (1.25 liters / minute) with fixation of CO2 (1 and 2 liters / minute). Catching CO2 into carbon dioxide by looking at growing biomass, and the yield content of oil in biomass. The results showed that there were significant differences in the growth patterns of microalgae given O2 aeration and CO2 fixation. Modified CHU 13 Detmer Modified media did not provide a significant difference to algal growth. With a large intensity of light with a medium that is sufficient to increase the growth of microalgae until it reaches the death phase.